Supporting the Innovation of Regions in the European Union through the Development of Smart Specializations Based on the Example of the Silesia Province - Dziembała , Małgorzata (Studia Oeconomica Posnaniensia, 2018)
Today, the primary factor shaping the development of regions and their competitiveness in a globalizing economy is the ability to create and diffuse innovation. The aim of a cohesion policy is to promote research and development as well as innovations in the regions, to ensure complementarity of support for innovation at various levels, and to fully exploit the potential of the regions. To this end, the strategies of smart specialization should be developed. The aim of the article is to indicate the importance of smart specialization strategies (policies) in the creation of the innovation capacity of different regions, with a particular focus on the Silesia province. The strategies of regional specializations in Poland should play an important role in transforming the economic structures of regions and creating their innovation potential in terms of global economy challenges, while fostering their competitiveness. Depending on the category of the regions, different approaches to smart specialization and a variety of applications can be identified. It also becomes necessary to take into account the experiences of other regions that represent similar structural characteristics.